2010
DOI: 10.1016/j.jff.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

β-Conglycinin (7S) and glycinin (11S) exert a hypocholesterolemic effect comparable to that of fenofibrate in rats fed a high-cholesterol diet

Abstract: Glycinin Fenofibrate Hypercholesterolemic diet Dyslipidemia Rats A B S T R A C TThe hypocholesterolemic effect of isolated soybean proteins and fenofibrate in rats was compared. Forty-five rats were divided into five groups: standard (STD; casein), high cholesterol (HC; STD plus 1% cholesterol/0.5% cholic acid), HC + b-conglycinin, HC + glycinin and HC + fenofibrate. The proteins and the drug were administered by gavage for 28 days. The proteins decreased total cholesterol (TC) and triacylglycerol (TG) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…The isolation procedure did not cause any change in the subunits and was important to obtain purified protein suitable for the in vivo studies [14,15]. Our previous results and those decribed by Duranti et al [13] have shown that the addition of 1% cholesterol and 0.5% cholic acid to the AIN-diet is sufficient to induce hypercholesterolemia and hypertriglyceridemia in rats.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The isolation procedure did not cause any change in the subunits and was important to obtain purified protein suitable for the in vivo studies [14,15]. Our previous results and those decribed by Duranti et al [13] have shown that the addition of 1% cholesterol and 0.5% cholic acid to the AIN-diet is sufficient to induce hypercholesterolemia and hypertriglyceridemia in rats.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, the atherogenic index (AI) of the hypercholesterolemic diet group (HC), in this experiment, was 8 times higher than that of rats on the casein standard diet [14], as also observed by other authors [10]. All treatments resulted in reductions in AI of the animals, the combination of 7S protein and fenofibrate (HC+7S+FF group) being the most efficient, followed by fenofibrate (HC+FF group), protein (HC+7S group), protein plus rosuvastatin (HC+7S+RO group) and rosuvastatin (HC+RO group), with falls of 81, 76, 57, 55 and 50%, relative to HC, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The extract was evaporated to dryness at room temperature and used for isolation of b-conglycinin and glycinin as previously described (Ferreira et al 2010). …”
Section: Extraction and Isolation Of B-conglycinin And Glycininmentioning
confidence: 99%
“…In particular, numerous studies have shown that soy foods are able to reduce total and lowdensity lipoprotein (LDL) cholesterol levels in highly and mildly hypercholesterolaemic subjects (Harland & Haffner, 2008;Jenkins et al, 2010;Sirtori, Eberini, & Arnoldi, 2007). Either in animals (Ferreira, Silva, Demonte, & Neves, 2010;Marazza, LeBlanc, Savoy de Giori, & Garro, 2013;Sirtori et al, 1984) or humans (Baum et al, 1998;Lovati et al, 1987), it has been demonstrated that this activity is linked to the modulation of LDL-receptors (LDLR), but the actual mechanism of action has not yet been understood in detail. Although isoflavones were initially considered the main factors responsible for the observed activity (Sirtori, Arnoldi, & Johnson, 2005), some following studies have addressed the possible role of soy proteins per se in cholesterolaemia reduction (Fukui et al, 2002;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%